2004
DOI: 10.1016/j.jvs.2004.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Stent-graft repair of traumatic thoracic aortic disruptions

Abstract: Stent-graft repair of traumatic thoracic aortic disruptions is technically feasible. Placement of a stiff wire in the right axillary artery and percutaneous left brachial artery access for arteriography are useful adjuncts during endograft deployment. Endovascular stent grafts may enable definitive repair or serve as a bridge until the patient is stable enough to undergo an operation, if necessary. This technique warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 24 publications
2
83
0
1
Order By: Relevance
“…In recent studies, the reported proximal fixation lengths have ranged between 22 and 28.5 mm (27). In the current study, the mean distance between the orifice of the left SCA and the thoracic aortic rupture was 23.5±6.1 mm.…”
Section: Discussionsupporting
confidence: 46%
“…In recent studies, the reported proximal fixation lengths have ranged between 22 and 28.5 mm (27). In the current study, the mean distance between the orifice of the left SCA and the thoracic aortic rupture was 23.5±6.1 mm.…”
Section: Discussionsupporting
confidence: 46%
“…Recent reports have shown that emergency repair of thoracic aortic disease with endovascular stent-grafts is a safe, effective and less invasive treatment option with technical success rates ranging from 90 to 100% and encouraging short-and mid-term results (Table 1) [5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the terms acute and chronic traumatic lesion is used incongruent in literature [6,13,18]. Nevertheless, the concomitant injuries seem to be the cause of mortality in patients treated with an endovascular stent graft [19][20][21][22]. Even in our cohort, the two cases of mortality were related to the contusion of the heart arising incurable arrhythmia.…”
Section: Discussionmentioning
confidence: 82%